THE USE OF CONTEXTUAL TEACHING LEARNING (CTL) MODEL TO IMPROVE STUDENT LEARNING OUTCOMES OF CLASS III DIVERSITY MATERIAL AT SD PLUS AL-FATHONAH MADLOTILAH, BEKASI DISTRICT - Dulyapit, Apit; Rahmah, Nur (PRODI PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN STKIP PGRI SUMENEP, 2023)
The problem of student learning outcomes in Civics subjects on social diversity, culture, and customs which are low and the average value has not reached the KKM, is the basis for this research. Based on the results of observations made by researchers, one of the obstacles faced in learning Civics is an ineffective learning model. To overcome this, researchers used the CTL (Contextual Teaching and Learning) learning approach toimprove Civics learning outcomes on the material of social diversity, culture, and customs in SD Plus Alfathonah Madlotilah, Bekasi Regency. The research was conducted in two cycles. Before carrying out the action, an initial test was held to find out the extent of knowledge possessed by students. The learning method uses the contextual teaching and learning (CTL) approach. The research subjects were third grade students of SD PLUS alfathonah Madlotilah, Bekasi Regency, consisting of 13 female students and 14 male students. Based on the results of the research that has been carried out in cycle I, the incompleteness is obtained 55.56% and changes to complete 44.44%, then in cycle II it increases to 100% or can be said to be perfect. So it can be concluded from this research by using the concept of Contextual Teaching and Learning the learning process has improved